KERJASAMA SISTER CITY KOTA YOGYAKARTA-DISTRIK COMMEWIJNE SURINAME DALAM BIDANG KEBUDAYAAN TAHUN 2011-2014 - Herning Suryo, Yusuf Akhmad Assegaff, Christy Damayanti & (Transformasi, 2015)
Sister city is the concept of acculturation two different city locations and political administration with the aim to establish the relationship of culture and social contract between residents. Yogyakarta city is one of the cities in Indonesia which Sister city activity is quite high. Yogyakarta City is a relatively active in Suriname Commewijne District. Sister city cooperation between the city of Yogyakarta and Commewijne District officially started with the signing of the MoU (Memorandum of Understanding) on 4 April 2011. The MoU Sister city of Yogyakarta and the Commewijne District agreed on cooperation in the fields of Culture, Tourism, Education, Agriculture, Health and Industry and Trade. Of all the areas of cooperation, the cultural sector is an area that stands out compared to other areas. This research using the theory of International Cooperation and the concept of Bilateral Relations and the research method used by researchers is the kind of qualitative research with data collection using data from interviews and literature. Researchers used primary data and secondary data.This Sister city Partnership lasted very active in the field of culture and a bridge towards improving bilateral relations. Realization of cooperation in the field of culture has been followed by the delivery of cultural delegations, both from the city of Yogyakarta to Commewijne District and viceversa. In this study the results show that cultural cooperation is to contribute in the improvement of bilateral relations and is able to promote the creative economy of Yogyakarta that having a Java character to the Republic of Suriname.Keyword: cooperation, culture, sisters city, district